PENGARUH PERILAKU ORGANISASI KOLEGIAL, UKURAN PENILAIAN KINERJA, DAN PENGELOLAAN KUALITAS SUMBER DAYA MANUSIA TERHADAP TINGKAT PRODUKTIVITAS PEGAWAI DINAS LINGKUNGAN HIDUP SURAKARTA - Wijayaningrum, Ayudya; Widiastuti, Erni (Universitas Of Surakarta, 2021)
This research aimed to determine and analyze the value of relation between collegial organizational behavior, performance appraisal measures, and management quality of human resources that can affect the productivity level of Dinas Lingkungan Hidup Surakarta employees, either partially and simultaneous. This research is focused on quantitative case study. Data obtained using the documentation and interview methods. Population in this research were 245 employees working in Dinas Lingkungan Hidup Surakarta. Twenty percent was used as a sample, so many as 49 respondents were obtained taking by random sampling techniques. Data in this research were tested by multiple linear regression analysis, t test, F test, and also coefficient of determination (R2). The result of this research are: 1). Collegial organizational behavior and performance appraisal measures as partially has a positive relation and significant effect. 2). Management quality of human resources as partially has a positive relation but isn’t significant. 3). Collegial organizational behavior, performance appraisal measures, and management quality of human resources as simultaneous has a significant on the productivity level of Dinas Lingkungan Hidup Surakarta employees. All of data analysis results supported by previous research, except the variable of management quality of human resources has not a significant effect on the productivity level of Dinas Lingkungan Hidup Surakarta employees. The reason is the higher somebody’s ages, the lower physical quality and healthy of employees, so that will be easier to affect management quality of human resources considering Dinas Lingkungan Hidup Surakarta has many elderly employees.